Biomechanical assessment of the ipsilesional upper limb in post-stroke patients during multi-joint reaching tasks: A quantitative study - Scano, Alessandro; Guanziroli, Eleonora; Mira, Robert M.; Brambilla, Cristina; Molinari Tosatti, Lorenzo; Molteni, Franco (Frontiers in Rehabilitation Sciences, 2022)
In post-stroke hemiplegic patients, investigating the ipsilesional limb may shed light on the upper limb motor control, impairments and mechanisms of functional recovery. To demonstrate that the performance of the ipsilesional limb in post-stroke patients is lower than healthy controls, 49 adults with ipsilateral limbs from hemiplegic patients were enrolled, and assessed with a kinematic and dynamic evaluation protocol on their ipsilesional upper limb during reaching movements. Measurements were repeated in the acute and subacute phases and compared to healthy controls. The ipsilesional limb presented different kinematic and dynamic performances. In fact, in the ipsilesional limb limited shoulder range of motion, shoulder energy and power were observed in patients, especially in the most impaired group. Patients also showed ipsilesional higher motor deficits in the acute phase with respect to the subacute one. The results of this study demonstrate ipsilesional upper limb impairments in post-stroke patients. Ipsilesional upper limb biomechanics adds significant measures for assessments based on multi-joints dynamics, showing specific relationship with the contralesional upper limb impairments and upper limb motor control after stroke.